Demand forecasting on supply chain using ML and NN - Hridi, Naoshin Anzum; Farhan, Md Sharior Hossain; Abed, Md. Junaed; Rafsan, Mohammad Nafiz Fuad (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.